Wildlife inventory from camera-trapping surveys in the Azores (Pico and Terceira islands) - Lamelas-López, Lucas (2020)
The present publication provides a dataset from five camera-trapping sampling campaigns on two islands of the Azorean archipelago (Pico and Terceira islands), between 2013-2018. This dataset was obtained as a by-product of campaigns designed for different purposes. The sampling campaigns were designed to: (i) study the ecology of introduced mammals; (ii) assess the impact of introduced mammals on native birds (Azores woodpigeon - Columba palumbus azorica and Cory's shearwater - Calonectris diomeda borealis), through nest predation; and (iii) obtain information about the impact of vertebrates on agricultural systems, particularly on Azorean traditional vineyards. A total of 258 sites and 47 nests were sampled using camera traps. These sampling campaigns provided a large data series that allowed the creation of a vertebrate wildlife inventory.